Romanticism and the Rural Community - White, S. author. aut Link
IX, 223 p.
Keywords: The proper organisation of rural communities was central to political and social debates at the turn of the eighteenth century, and featured strongly in the 1790s political polemic that influenced so many Romantic poets and novelists. This book investigates the representation of the rural village and country town in a range of Romantic texts.